Effect of antibacterial nanocomposite film on the preservation of cheese - LI,Yana (2022)
Abstract High density polyethylene (HDPE) and nano-ZnO were used to prepare nano-ZnO/HDPE composite film with a nano-ZnO content of 0.5wt%. The morphology, mechanical, barrier and antibacterial properties, as well as the preservation to cheese of the films were studied. The results showed that the ZnO nanoparticles had a good dispersion in HDPE matrix so that the improvement of the mechanical, barrier and antibacterial performances of the film was achieved after the addition of nano-ZnO to HDPE. In comparison to cheese packaged in HDPE bags, it was found that the sensory score of the cheese in nano-ZnO/HDPE bags increased from 66.6 to 73.7 and the pH of cheese was closer to the standard sample at storage time of 7d. Furthermore, nano-ZnO/HDPE inhibited effectively the increase of the total bacterial count (TBC) on cheese contrast of HDPE. That indicates the prepared nano-ZnO/HDPE is potential in cheese packaging to extend the shelf life.